1986
DOI: 10.1016/s0022-5347(17)45936-2
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration Biopsy of the Prostate Gland: A Study of 103 Cases With Histological Followup

Abstract: Fine needle aspiration specimens of the prostate gland were compared to histological material in 103 patients. The sensitivity was 95 per cent, specificity 97 per cent and efficiency 87 per cent. Initial core needle biopsy compared to the final histological diagnosis in this study had a sensitivity of 76 per cent, specificity 100 per cent and efficiency 71 per cent. Fine needle aspiration by a well trained cytopathologist is less traumatic, and has fewer side effects and a higher sensitivity rate than conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…According to The John Hopkins Experience, only 55% patients who met the criteria for RP had tumors that were organ confined, and in approximately 10% of cases the disease involved regional lymph nodes or seminal vesicles. 97 Correlation of cytological grading with the Gleason score has been published elsewhere 59,63,67,70,72,[77][78] and the accuracy of digitally guided transrectal FNA has been tested in comparative studies with thick and ultrasound-guided thinneedle core biopsies; both methods have equal sensitivity and specificity, and false positives are rare to nonexistent: 7,8,[15][16]27,30,[32][33]36,[55][56]59,[61][62][68][69]71,73,76,92,93,95 FNA passed this scrutiny with honors and was deemed suitable to perform a confident diagnosis of prostate cancer. According to Tannenbaum,78 when an appropriate number of samples are obtained from palpable abnormal prostates, the detection rate for cancer is the same for both aspiration and core biopsies.…”
mentioning
confidence: 99%
“…According to The John Hopkins Experience, only 55% patients who met the criteria for RP had tumors that were organ confined, and in approximately 10% of cases the disease involved regional lymph nodes or seminal vesicles. 97 Correlation of cytological grading with the Gleason score has been published elsewhere 59,63,67,70,72,[77][78] and the accuracy of digitally guided transrectal FNA has been tested in comparative studies with thick and ultrasound-guided thinneedle core biopsies; both methods have equal sensitivity and specificity, and false positives are rare to nonexistent: 7,8,[15][16]27,30,[32][33]36,[55][56]59,[61][62][68][69]71,73,76,92,93,95 FNA passed this scrutiny with honors and was deemed suitable to perform a confident diagnosis of prostate cancer. According to Tannenbaum,78 when an appropriate number of samples are obtained from palpable abnormal prostates, the detection rate for cancer is the same for both aspiration and core biopsies.…”
mentioning
confidence: 99%
“…Similar observations have been reported by Couture et al, Kline et al, Ljung et al, Koltz et al and Brenner et al . [16,17,18,19,20] Al Abadi reviewed the pertinent literature, notably papers by Bruin et al and his own previous publication and concluded that FNA was more accurate, less tedious to the patient and much cheaper than the core biopsy. [21] Hermida et al reported sensitivity of 96%, specificity 96%, positive predictive value 91%, negative predictive value 93% and efficacy 92%.…”
Section: IVmentioning
confidence: 99%
“…177 Liung and colleagues reported a lower false negative rate (3 from 41 'benign' cases); however, there were no details of their study population. 180 These studies suggest a poor sensitivity for aspiration cytology. Furthermore, the value of actively trying to identify prostatic tumours in TURP patients is questionable.…”
Section: Tumour Detectionmentioning
confidence: 99%